2018
DOI: 10.3847/1538-4357/aaec69
|View full text |Cite
|
Sign up to set email alerts
|

Possible Phase-dependent Absorption Feature in the X-Ray Spectrum of the Middle-aged PSR J0659+1414

Abstract: We report on the energy-resolved timing and phase-resolved spectral analysis of X-ray emission from PSR J0659+1414 observed with XMM-Newton and NuSTAR. We find that the new data rule out the previously suggested model of the phase-dependent spectrum as a three-component (2 blackbodies + power-law) continuum, which shows large residuals between 0.3 − 0.7 keV. Fitting neutron star atmosphere models or several blackbodies to the spectrum does not provide a better description of the spectrum, and requires spectral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
50
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 65 publications
12
50
4
Order By: Relevance
“…Using XMM-Newton and NICER we firstly established an X-ray ephemeris for the time interval 2015 to 2020, which connects all X-ray observations in this period without cycle count alias and phase shifts. The mean eROSITA spectrum clearly reveals an absorption feature originating from the star at 570 eV with a Gaussian σ of about 70 eV, tentatively identified earlier in a long XMM-Newton observation (Arumugasamy et al 2018). A second absorption feature, described here as an absorption edge, occurs at 260 − 265 eV.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Using XMM-Newton and NICER we firstly established an X-ray ephemeris for the time interval 2015 to 2020, which connects all X-ray observations in this period without cycle count alias and phase shifts. The mean eROSITA spectrum clearly reveals an absorption feature originating from the star at 570 eV with a Gaussian σ of about 70 eV, tentatively identified earlier in a long XMM-Newton observation (Arumugasamy et al 2018). A second absorption feature, described here as an absorption edge, occurs at 260 − 265 eV.…”
supporting
confidence: 77%
“…The most recent account of the phase-averaged X-ray spectrum of B0656 was given by Zharikov et al (2021), who on the one hand confirmed the earlier spectral model by Arumugasamy et al (2018), but also refined it through the inclusion of infrared/optical/ultraviolet data (IR/opt/UV). The spectral energy distribution established in this paper is best described by a broken power law from the magnetosphere plus the double blackbody with superposed absorption line at ∼0.5 keV originating from the stellar surface.…”
Section: Introduction Psr B0656+14 (Hereafter B0656mentioning
confidence: 83%
See 2 more Smart Citations
“…So, among the remaining 9 pulsars, none of them show definitive evidence for isotropic emission of a BB. On the contrary, for pulsars with high S/N data, the pulse profiles are sharper and non-sinusoidal in the energy range where the polar cap emission dominates often with high pulsed fractions or increasing pulsed fraction with energy (PSR B0656+14; De Luca et al 2005;Arumugasamy et al 2018De Luca et al 2005Kargaltsev et al 2005). These are indicative of beamed (anisotropic) emission significantly deviating from a BB.…”
Section: Discussionmentioning
confidence: 99%